All-Ceramic Crowns Over Single Implant Zircon Abutment. Influence of Young's Modulus on Mechanics - Freitas Júnior, Amilcar Chagas [UNESP]; Rocha, Eduardo Passos [UNESP]; Santos, Paulo Henrique dos [UNESP]; de Almeida, Erika Oliveira [UNESP]; Anchieta, Rodolfo Bruniera [UNESP] (Lippincott Williams & Wilkins, 2010)
Purpose: The aim of this study was to evaluate the influence of different Young moduli of the ceramic crown on the distribution of tensions in the region of the abutment-crown interface by making use of 2D finite element analysis.Materials: Two representative models of a sagittally sectioned maxilla were built through AutoCad program showing an implant in the region of the upper central incisor and were restored by means of IPS e. max Press or Procera AllCeram on zircon abutment. Numerical analysis (Ansys 10.0) was performed under 2 loading conditions (50 N): on the lingual face, at 45 degrees with the implant's long axis (L1) and perpendicular to the incisal edge (L2). The von Mises equivalent stress (sigma(vM)) and maximum principal stress (sigma(max)) were obtained.Results: It was noticed that, independent of the restoring system, the maximum sigma(vM) values were in the incisal region of the cementation interface for both loading conditions. The IPS e.max Press system showed higher sigma(vM) on the adhesive interface with higher L1 influence. The same behavior was also observed as regards the sigma(max) variation.Conclusions: It was concluded that a restoring system with a lower Young modulus shows higher stress concentration on the abutment-crown interface when cemented on an abutment with a high Young modulus. Thus, IPS e.max Press system provides higher stress concentration in the resin cement layer than Procera AllCeram system, suggesting that the resin cement layer shows lower failure risk when the Procera crown is used. (Implant Dent 2010;19:539-548)
Keywords: dental implants; fixed partial denture; biomechanics; finite element analysis